Piper sarmentosum (Daun kaduk) induced apoptosis via mitochondrial pathway in human lung adenocarcinoma cells, A549 - Sirajudeen, Azila; Mohd Ali, Aisyah Hanani; Abdul Ghani, Radiah (2016)
Lung cancer has been reported as one of the top diseases in the world. Current cancer treatments like chemotherapy do not completely cure cancer and cause some side effects to the patient. Therefore, alternative strategies are being explored for cancer treatment and one of them is local herbs investigation. In relation to this, Piper sarmentosum (daun kaduk) has received an attention due to its’ anti-cancer properties. It has been reported that both herbs induce anti-proliferative effects in human lung carcinoma cells, A549. Besides, one of the characteristics of anticancer herbs is the ability to induce cell death through apoptosis, which cause little side effects to the normal cells. In this study, the cell cycle profile and mechanism of cell death induced by daun kaduk was investigated using flow cytometer. The cell cycle profile changes were observed using Propidium iodide staining and it is found that P.sarmentosum arrested at G0/G1 phase in A549 cycles. Meanwhile, the Annexin V analysis revealed that P. sarmentosum showed significantly induction of apoptotic cells compared to untreated A549 cells. Furthermore, caspase analysis showed that P. sarmentosum induces apoptosis through mitochondrial pathway, by the activation of caspase 3 and caspase 9 significantly. Meanwhile, cytochrome c analysis reveals that P. sarmentosum induce a mitochondrial pathway of cell death mechanism by release of cytochrome c. Based on these preliminary findings, P. sarmentosum has a great potential as a dietary cancer treatment for lung cancer and may be used for lung cancer pharmacotherapy in clinical settings in future.